PENELUSURAN SEJARAH INSTRUMEN GAMBUS DALAM ANSAMBEL MUSIK MELAYU DI KABUPATEN SANGGAU - MUhammad Julian Sujatmiko; Ismunandar Ismunandar; CHiristianly Yeri Silaban (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2017)
Abstract This research was background caused of there is no documentation about when gambus instrument being apart of Malay music ensemble at Sanggau city. The purpose of this research was to description about history of gambus on malay ensemble music at Sanggau City and how the developed of gambus in malay music ansamble from past to the present. The method that used was descriptive method with qualitative form. The approaching of research was historically. Data source used primer data. Data research was the interview result, observation result, and documentation result about history of gambus instrument on malay music ensemble. The result of this research was an efforts that did in historical investigation  of gambus instrument on malay music ensemble by meet with the informant who was a musician of malay music ensemble, description the history about gambus instrument being apart of malay music ensemble, and to description of gambus instrument development on malay music ensemble.      Keyword: History, Gambus, Malay Music ensemble